Geography 2.4 - Evans, Jane Allison; Osborne, Cheryl (Always learning, 2011)
Introduction to geography -- revision of basic skills -- Statistical and visual techniques in geography -- Fieldwork sills -- Skills at a global scale -- Skills at a continental scale -- Skills at a national scale -- Skills at a local scale